Who is concerned about terrorist attacks? A religious profile - Dinis, Maria Alzira Pimenta (Social Sciences, 2019)
As part of the study on the psychological impact of terrorist acts on ordinary people, the objective of this study is to understand if religious identity protects individuals from feeling concerned about the possibility of terrorist attacks. The study was based on a sample from the World Values Survey, wave 6 (2010-2014), of 30,446 citizens of countries whose dominant religion is Christianity. According to the concern felt regarding the possibility of becoming the target of a terrorist attack, a religious profile was identified. Most of the sample reported high levels of worry about terrorist attacks. The most religious respondents, more faithful and more devoted to religious practices, are more worried about the occurrence of terrorist attacks. Opposite to what is mostly found in the literature, religion does not act as a protective barrier to the primary objective of terrorism, which consists in the use of violence to create fear. People worried about the probability of becoming a target in terrorist attacks are also victims of terrorism.info:eu-repo/semantics/publishedVersio